Removal of hydrogen sulfide from coke oven gas by catalytic oxidative absorption in a rotating packed bed. (15th September 2017) - Zou, Haikui; Sheng, Miaopeng; Sun, Xiaofei; Ding, Zihao; Arowo, Moses; Luo, Yong; Zhang, Liangliang; Chu, Guangwen; Chen, Jian-Feng; Sun, Baochang
Highlights: Catalytic oxidative absorption of H2 S from a simulated COG in a RPB was explored. Na2 CO3 solution doped with a commercial "888" catalyst was used as the absorbent. Effect of operating conditions on the removal efficiency of H2 S was studied. RPB exhibited higher H2 S removal efficiency than the compared packed column. Abstract: The shortage of low-sulfur coking coal will bring about an increasingly high hydrogen sulfide (H2 S) in the coke oven gas (COG) in the near future. This work investigated the removal of hydrogen sulfide (H2 S) from a simulated coke oven gas( COG) by catalytic oxidative absorption in a rotating packed bed (RPB). Sodium carbonate (Na2 CO3 ) solution doped with 20 mg L −1 of a commercial "888" catalyst was used as the absorbent. The removal efficiency of H2 S was evaluated under various operating conditions including rotation speed of the RPB ( N ), liquid-gas ratio ( L / G ), inlet H2 S concentration ( c H 2 S, in ), temperature ( T ) and Na2 CO3 concentration ( c Na 2 CO 3 ) in an attempt to optimize the conditions. The results were validated by comparison with those of separate experiments conducted in a packed column comprising a high-efficiency laboratory packing of Dixon rings. The comparison results reveal that the RPB exhibited higher H2 S removal efficiency than the packed column, indicating it as an efficient gas-liquid contactor with a greater potential to remove H2 S from COG.